"\\displaystyle\n\n\n (y\u00b2 -1)\\mathrm{d}x -2\\mathrm{d}y =0\\\\\n\ny^2 - 1 - 2y' = 0\\\\\n\ny^2 - 1 = 2y' \\\\\n\n\n\n\\frac{2}{y^2 - 1} \\,\\mathrm{d}y = \\mathrm{d}x\\\\\n\n\\int\\frac{2}{y^2 - 1} \\,\\mathrm{d}y = \\int\\mathrm{d}x\\\\\n\n\n\\frac{1}{2}\\cdot 2 \\ln\\left(\\frac{y - 1}{y + 1}\\right) = x + C\\\\\n\n\\frac{y - 1}{y + 1} = e^{x + C}\\\\\n\n\n\\frac{y - 1}{y + 1} = Ae^{x}\\\\\n\n\ny - 1 = A(y + 1)e^{x}\\\\\n\n\ny(1 - Ae^{x}) = Ae^{x} + 1 \\\\\n\n\ny = \\frac{1 + Ae^{x}}{1 - Ae^{x}}"
Comments
Leave a comment